UNVEILING THE ROLE OF TEACHER PROFESSIONAL IDENTITY IN TEACHER RETENTION: A QUALITATIVE INQUIRY - Maria Dewi Rosari (IKIP Siliwangi, 2024)
This research investigates the correlation between the professional identity profiles of English Course teachers and their retention rates. Drawing upon previous research, the study examines how elements of teacher professional identity—namely job satisfaction, occupational commitment, work motivation, and self-efficacy—contribute to teachers' willingness to remain in their current positions. Utilizing a qualitative approach, data were collected from English Courses teachers in Yogyakarta Province, focusing on various subgroups such as English Course size, gender, and teaching experience. Findings reveal that while overall retention rates are high across all subgroups, differences emerge in the strength of professional identity elements and retention rates among teachers from different English Course sizes and demographics. Notably, work environment emerges as a crucial factor influencing teacher professional identity and retention rates, with supportive atmospheres positively impacting teachers' commitment, motivation, and self-efficacy. The study underscores the significance of understanding how professional identity elements interact with contextual factors to shape teacher retention in non-formal education settings. Future research should explore additional contextual variables and interventions to further enhance teacher retention strategies in this sector.